2006
DOI: 10.1073/pnas.0600584103
|View full text |Cite
|
Sign up to set email alerts
|

Nonconscious semantic processing of emotional words modulates conscious access

Abstract: Whether masked words can be processed at a semantic level remains a controversial issue in cognitive psychology. Although recent behavioral studies have demonstrated masked semantic priming for number words, attempts to generalize this finding to other categories of words have failed. Here, as an alternative to subliminal priming, we introduce a sensitive behavioral method to detect nonconscious semantic processing of words. The logic of this method consists of presenting words close to the threshold for consc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 52 publications
3
92
1
1
Order By: Relevance
“…When target-mask SOA is varied, perception of the target typically follows a nonlinear sigmoid curve, with a critical SOA of about 50 msec (Del Cul et al, 2007), slightly shorter than the present critical time of about 80 msec. The masking threshold can also be shifted by higher-level factors such as whether the masked stimulus is an emotional word (Gaillard et al, 2006). These parallels suggest that masking and temporal integration phenomena may be related.…”
Section: Discussionmentioning
confidence: 81%
“…When target-mask SOA is varied, perception of the target typically follows a nonlinear sigmoid curve, with a critical SOA of about 50 msec (Del Cul et al, 2007), slightly shorter than the present critical time of about 80 msec. The masking threshold can also be shifted by higher-level factors such as whether the masked stimulus is an emotional word (Gaillard et al, 2006). These parallels suggest that masking and temporal integration phenomena may be related.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, and most importantly, we have used imaging to show that activity in the mid-dorsolateral prefrontal cortex is associated with the priming effect. These findings, together with previous research on the depth of subliminal priming (Dehaene et al, 1998;Hannula et al, 2005;Naccache et al, 2005;Gaillard et al, 2006), challenge critics to reconsider the limits of unconscious processing.…”
Section: Discussionmentioning
confidence: 84%
“…Inspired by recent advances in neuroimaging research that also draw attention to the strength and depth of subliminal priming (Dehaene et al, 1998;Hannula et al, 2005;Naccache et al, 2005;Gaillard et al, 2006), we attempted to create a situation in which subliminally presented stimuli influence the establishment of tasksets. This constitutes a strong test for the traditional assumption that higher cognitive functions require consciousness (Jack and Shallice, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Non-conscious information can modulate performance in many cognitive tasks, eg. object recognition (Stoerig & Cowey, 1997), extraction of the meaning of words (Gaillard et al, 2006;; Van den Bussche, Notebaert, & Reynvoet, 2009), categorization (Van den Bussche & Reynvoet, 2007), emotional processing (Whalen et al, 1998), action planning and execution (Binsted, Brownell, Vorontsova, Heath, & Saucier, 2007). Recently, it has been reported that monetary rewards affected subjects' motivation in a force task (Pessiglione et al, 2007), a finger-tapping task (Bijleveld, Custers, & Aarts, 2010 and a switch task (Capa, Bouquet, Dreher, & Dufour, 2012) even though participants were unaware of the reward.…”
Section: Introductionmentioning
confidence: 99%